2021
DOI: 10.1029/2021gl095090
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Proton Aurora Driven by EMIC Pc1 Wave: PWING, Swarm, and NOAA POES Multi‐Instrument Observations

Abstract: into the Earth's atmosphere via pitch angle scattering induced by resonant wave-particle interactions. Observations of precipitating protons (>30 keV) associated with Pc1 wave were first reported by Yahnina et al. (2000) using data from the NOAA-12 satellite and the Sodankylä ground magnetometer. Yahnina et al. (2003) investigated energetic proton precipitation with/without lower energy (<20 keV) counterparts during Pc1 wave activity and showed that the type of Intervals of Pulsations with Diminishing Periods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 50 publications
(71 reference statements)
3
22
0
Order By: Relevance
“…Ozaki et al (2018) reported 1 Hz range modulation of IPAs and concluded that the modulation was due to intermittent proton precipitation or sub/ relativistic electrons scattered by repetitive bursts of fine-structured EMIC waves. EMIC waves that cause IPA work for MeV electron scattering (e.g., Miyoshi et al, 2008) and the density irregularity of the topside ionosphere (Kim et al, 2021).…”
mentioning
confidence: 99%
“…Ozaki et al (2018) reported 1 Hz range modulation of IPAs and concluded that the modulation was due to intermittent proton precipitation or sub/ relativistic electrons scattered by repetitive bursts of fine-structured EMIC waves. EMIC waves that cause IPA work for MeV electron scattering (e.g., Miyoshi et al, 2008) and the density irregularity of the topside ionosphere (Kim et al, 2021).…”
mentioning
confidence: 99%
“…IPAs have been observed in connection with EMIC wave activities (e.g., Sakaguchi et al, 2007Sakaguchi et al, , 2008Sakaguchi et al, , 2015Zhang et al, 2008;Yuan et al, 2010;Kim et al, 2021). In this subsection, we shall examine the potential EMIC wave activities from both ground-based and in-situ magnetometer data.…”
Section: Ground and In-situ Magnetometer Data: Evidence Of Electromag...mentioning
confidence: 98%
“…Using data from the multi-wavelength all-sky-imagers (ASI) and induction magnetometers, Sakaguchi et al (2007; investigated the "isolated proton auroras" in the evening sector and found them coincident with Pc1 geomagnetic pulsations. Those detached/isolated proton arcs/blob/spots, despite their differences in shapes and fine structures, are now often deemed to owe their source mechanisms to the electromagnetic ion cyclotron (EMIC) wave and its resulting pitch-angle scattering of ring-current ions in the inner magnetosphere (e.g., Immel et al, 2005;Sakaguchi et al, 2007Sakaguchi et al, , 2008Sakaguchi et al, , 2015Yahnin et al, 2007;Yuan et al, 2010;Liang et al, 2014;Kim et al, 2021;Shumko et al, 2022). EMIC waves are generated in the equatorial region of the plasmaspheremagnetosphere by internal wave-particle interaction with ringcurrent ions (Fraser et al, 2005;Jordanova et al, 2007;Usanova et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al. (2020, 2021) reported that IPAs with EMIC waves were accompanied by weak field‐aligned currents using ground‐based all‐sky imager and the Swarm and POES satellites, and Pc1 geomagnetic pulsations were accompanied by ionospheric density variations of the same period.…”
Section: Introductionmentioning
confidence: 99%